Healthcare-seeking behaviors and barriers among medical students in Egypt: a national cross-sectional study - Ghada O. El-Khawaga; Yusof M. Omar; Mohamed Elsaadany; Mohamed Ghazy; Amr Khaled Abdelaal; Mahmoud Hekal; Abdel-Hady El-Gilany; H. S. B. team of collaborators (BMC Public Health, 2025)
Abstract Background Medical students are particularly vulnerable to acquiring various health conditions due to the nature of their education but often hesitate to consult doctors and resort to self-managing their illnesses. This study aims to examine the healthcare-seeking behaviors and barriers among medical students in Egypt. Methods This cross-sectional study involved a convenience sample of 1,535 medical students from 12 public universities across Egypt. Data on healthcare-seeking behaviors, barriers, and associated factors were collected using an online survey distributed through official university channels and social media platforms. Logistic regression analysis was used to identify factors associated with consulting a doctor when experiencing health problems. Results Only 52.2% of participants reported consulting doctors when ill. Participants from rural backgrounds (COR = 0.69, CI: 0.51–0.93), those facing barriers to healthcare (COR = 0.80, CI: 0.66–0.98), with less than sufficient income (COR = 0.61, CI: 0.46–0.81), or a non-working mother (AOR = 0.76, CI: 0.58–0.99) were less likely to consult a doctor. In contrast, participants with more than sufficient income (COR = 1.35, CI: 1.02–1.78), a parent in healthcare (AOR = 13.18–17.31, CI: 6.87–36.35), or who exercised regularly (AOR = 1.48, CI: 1.09–2.01) were more likely to consult a doctor. A substantial proportion of students reported relying on past experiences with the illness (54.1%), using the Internet (46.8%), and self-diagnosing (36.2%). The most common reported barriers to seeking healthcare were lack of time (29.2%), long wait times (22.7%), and academic concerns (12%). A history of feeling uncomfortable or discriminated against when seeking healthcare was reported by 19.5% of participants. Conclusion Many medical students in Egypt engage in self-diagnosis and self-management rather than consulting doctors when ill. Addressing healthcare barriers is crucial for encouraging appropriate care-seeking behaviors within this population.